2012
DOI: 10.4049/jimmunol.1103708
|View full text |Cite
|
Sign up to set email alerts
|

EWI-2 Association with α-Actinin Regulates T Cell Immune Synapses and HIV Viral Infection

Abstract: EWI motif-containing protein 2 (EWI-2) is a member of the Ig superfamily that links tetraspanin-enriched microdomains to the actin cytoskeleton. We found that EWI-2 colocalizes with CD3 and CD81 at the central supramolecular activation cluster of the T cell immune synapse. Silencing of the endogenous expression or overexpression of a cytoplasmic truncated mutant of EWI-2 in T cells increases IL-2 secretion upon Ag stimulation. Mass spectrometry experiments of pull-downs with the C-term intracellular domain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 71 publications
1
50
0
Order By: Relevance
“…In accordance, activation of the actin-severing protein cofilin has been associated with enhanced HIV entry (26). Moreover, both removal of the bundling activity or siRNA knockdown of ␣-actinin, an actin microfilament cross-linker, increase HIV-1 infection (30). In addition, knockdown of proteins that link the actin cytoskeleton with the inner leaflet of the plasma membrane, such as talin and vinculin, have also been related with higher HIV-1 infection (31).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…In accordance, activation of the actin-severing protein cofilin has been associated with enhanced HIV entry (26). Moreover, both removal of the bundling activity or siRNA knockdown of ␣-actinin, an actin microfilament cross-linker, increase HIV-1 infection (30). In addition, knockdown of proteins that link the actin cytoskeleton with the inner leaflet of the plasma membrane, such as talin and vinculin, have also been related with higher HIV-1 infection (31).…”
mentioning
confidence: 67%
“…Clustering of CD4/CXCR4 has been suggested to depend on their incorporation into tetra-spanin-enriched microdomains (14 -16, 62) and to require cholesterol-enriched domains (46,54,55), attesting the importance of membrane microdomains for HIV-1 entry. Tetraspanin-enriched microdomains are linked to actin cytoskeleton through actin-binding proteins ERMs and ␣-actinin (30,63). ERMs and filamin-A, another actin-binding protein, are known to facilitate CD4/CXCR4 clustering during HIV-1 attachment and promote viral infection (18,20).…”
Section: Discussionmentioning
confidence: 99%
“…Immunoglobulin superfamily (IgSF) proteins such as EWI-2, EWI-F, ICAM-1, or VCAM-1, which are direct partners of tetraspanins CD9 and CD81, also present binding sites for actin-linking ERM proteins (33, 34). A proteomic study in human primary lymphoblasts and their derived EVs identified the association of CD81 with a large number of interacting partners, including alpha-actinin (35, 36). In the activation and adhesion of T cells, an inducible association of CD82 with the cytoskeletal matrix has been observed, so that CD82 induces spreading and development of membrane extensions, involving actin polymerization and contributing to T cell activation via their cytoplasmic domain (37).…”
Section: Tetraspanin Structure: the Key For Their Involvement In So Mmentioning
confidence: 99%
“…B cells (Raji or Hom2) were loaded with the CMAC tracker and loaded with SEE (0.5 to 1 g/ml) or HA peptide (100 to 200 g/ml), as appropriate (41). J77 or CH7C17 T cells were mixed with Raji or Hom2 B cells (1:1), centrifuged at low speed to favor conjugate formation, and incubated at 37°C for the indicated periods of time.…”
Section: Methodsmentioning
confidence: 99%